Recubrimiento de carbono símil diamante depositados en diferentes sustratos metálicos. Estudio de su comportamienti ttribomecanico y su resistencia a la corrosión en base a los parametros del proceso de deposición - Chicahuala Casabone, Alejandro (2020)
DLC coatings have attracted the interest of many researches due to their unique combination of properties. They are often used in various applications as protective coatings because of their excellent low friction, high wear resistance and chemical inertness. The focus of this work was to analyse tribological, mechanical and anti-corrosive properties of coatings varying in chemical composition, substrate material, surface treatment and deposition process parameters. One of the mail goals was to evaluate a possible effect of the silicon doping on the corrosive behaviour of the coated samples regarding a possible change in the coating electrical conductivity, but due to the 2020 COVID-19 pandemic this study was not possible to complete. In the present work, thick (~30µm) and thin (~3µm) Silicon doped DLC (a:C:H:Si) and a Silicon free DLC (a:C:H) were deposited on nitrided or non-nitrided low alloyed and stainless steels, with a thin or thick Silicon interlayer. The DLC coatings properties were characterized with the following techniques: nanoindentation, scratch test, calogrinding and pin on disk were used for tribomechanical characterization; Raman spectroscopy and confocal microscopy were used to characterize the DLC coating molecular structure and its superficial roughness; corrosion behaviour was analysed after immersion and salt spray chamber tests were performed, optical microscopy, confocal microscopy, scanning electron microscopy and energy dispersive spectroscopy were used for a qualitative analysis of the corrosion properties of the DLC coatings. In order to effectively compare the different exhibited behaviours regarding corrosion behaviour, the materials selection weighted property index method (WPIM) was applied. The coating thickness and its silicon content resulted the ruling factors to achieve the best corrosion resistance. This effect was mainly related to their synergistic effect in decreasing the passing-through defect density of the DLC coating. The substrate’s corrosion resistance also plays a major role, since plasma nitrided AISI 304 coated samples only suffered corrosion damage on the nitriding edge effect zone, a plasma nitriding process generated defect. With the Raman spectra results of the DLC coatings it was possible to estimate their molecular structure. The silicon doped coatings had lower hydrogen content and sp bonds fraction, but since silicon substitution promotes the formation of Si-C and C-C sp 3 bonds, an increase in the coating hardness was measured. Additionally, the lower bias voltage in the silicon doped coating’s deposition process was related to a decrease in the coating’s defect density. Besides the hardness increasing effect of the silicon doping variable, the scratch testing adherence results and their fractographic behaviour was studied. The adherence between the substrate and the DLC coating increased with the coating’s thickness, due to an increased load carrying capacity, and its superficial roughness, mainly related to the substrate roughness increase after the plasma nitriding process. Mail de los autores Alejandro Chicahuala Casabone <alejandro.chicahuala@gmail.com>